Systemic lupus erythematosus: state of the art on clinical practice guidelines. (23rd January 2019) - Tamirou, Farah; Arnaud, Laurent; Talarico, Rosaria; Scirè, Carlo Alberto; Alexander, Tobias; Amoura, Zahir; Avcin, Tadej; Bortoluzzi, Alessandra; Cervera, Ricard; Conti, Fabrizio; Cornet, Alain; Devilliers, Hervé; et al.
Abstract : Systemic lupus erythematosus (SLE) is the paradigm of systemic autoimmune diseases characterised by a wide spectrum of clinical manifestations with an unpredictable relapsing-remitting course. The aim of the present work was to identify current available clinical practice guidelines (CPGs) for SLE, to provide their review and to identify physicians' and patients' unmet needs. Twenty-three original guidelines published between 2004 and 2017 were identified. Many aspects of disease management are covered, including global disease management, lupus nephritis and neuropsychiatric involvement, management of pregnancies, vaccinations and comorbidities monitoring. Unmet needs relate with disease management of some clinical manifestations and adherence to treatment. Many patient's unmet needs have been identified starting with faster diagnosis, need for more therapeutic options, guidelines on lifestyle issues, attention to quality of life and adequate education.